Surgery for femoral metastases: results of procedure allocation according to patient-prognosis. (March 2020) - Tanaka, Atsushi; Katagiri, Hirohisa; Murata, Hideki; Wasa, Junji; Miyagi, Michihito; Honda, Yosuke; Takahashi, Mitsuru
Abstract : Aims: The aim of this study is to evaluate the clinical results of operative intervention for femoral metastases which were selected based on expected survival and to discuss appropriate surgical strategies. Methods: From 2002 to 2017, 148 consecutive patients undergoing surgery for femoral metastasis were included in this study. Prognostic risk assessments were performed according to the Katagiri and revised Katagiri scoring system. In general, the low-risk group underwent resection and reconstruction with endoprosthetic replacement (EPR), while the high-risk group underwent internal fixation (IF) and radiation therapy. For the intermediate-risk group, the operative choice depended on the patient's condition, degree of bone destruction, and radio-sensitivity. Overall survival, local failure, walking ability, and systemic complications were evaluated. Results: A total of 83 patients underwent EPR (low-risk, 23%; intermediate-risk, 60%; high-risk, 17%) and 65 patients underwent IF (low-risk, 0%; intermediate-risk, 32%; high-risk, 68%). The one-year survival rate was 71% for EPR and 15% for IF (p < 0.001). The one-year local failure-free survival was 93% for EPR and 67% for IF, and the two-year and five-year local failure-free survival for EPR were both 88% (p = 0.016). Although the ambulatory rate was 99% for EPR and 60% for IF, the median time to ambulation was shorter in the IF (EPR, 28 days, interquartile range (IQR) 25 to 35; IF, 23 days, IQR 18 to 28; p < 0.001) The cause of non ambulation was mainly due to progression of cancer (89%). The rate of systemic complications was comparable between the two groups (EPR, 18%; IF, 22%; p = 0.598). Conclusion: Selective use of EPR where survival is expected to be good offers correspondingly good long-term results. IF is less invasive with shorter treatment period, which is beneficial for patients with short-term expected survival. Prognosis is an important indicator in selecting operative procedures for femoral metastasis. Cite this article: Bone Joint J 2020;102-B(3):285–292